O-018 Variability in Response to a 75mg Daily Clopidogrel Dose in a Cohort of 90 Patients Undergoing Endovascular Treatment of Unruptured Cerebral Aneurysms. (14th July 2013) - Almandoz, J. Delgado; Kadkhodayan, Y; Scholz, J; Crandall, B; Fease, J; Anderson, R; Tubman, D
Abstract : Background and Purpose: Recent studies have suggested that variability in response to clopidogrel therapy may explain some of the thromboembolic and hemorrhagic complications encountered after endovascular treatment of cerebral aneurysms with flow-diversion or stent-assistance. This study aims to determine the variability in response to a 75mg daily clopidogrel dose measured with VerifyNow in a cohort of patients undergoing endovascular treatment of unruptured cerebral aneurysms. Methods: We performed a retrospective review of all patients who were started on a daily 75mg clopidogrel dose 7 to 10 days prior to endovascular treatment of a cerebral aneurysm and had the response to clopidogrel therapy measured with VerifyNow prior to the procedure over a 15-month period. Baseline clinical characteristics, concurrent medications and routine pre-operative laboratory values were collected. Changes in response to the daily 75mg clopidogrel dose in patients who underwent follow-up VerifyNow testing were also recorded. The target P2Y12 receptor inhibition range was 60–240 P2Y12 reaction units (PRU), with a PRU>240 considered a hypo-response to clopidogrel therapy (P2Y12 receptor under-inhibition), and a PRU<60 considered a hyper-response to clopidogrel therapy (P2Y12 receptor over-inhibition. Results: Ninety patients were included in the study, 66 female (73.3%) and 24 male (26.7%). Mean age was 57.4 years (median 59.9 years, range 25–82 years). Mean pre-procedure PRU value after 6–9 75mg clopidogrel doses was 140.1 (median 143 PRU, range 3–399 PRU). Eighteen patients exhibited a hyper-response to clopidogrel therapy (20%, PRU<60) and 14 patients exhibited a hypo-response to clopidogrel therapy (15.6%, PRU>240, figure). There was a trend toward an increased likelihood of a hyper-response to clopidogrel therapy among female patients (24.2%) compared to male patients (8.3%, p-value 0.14). Overall, 39.4% of female patients and 25% of male patients were outside the target P2Y12 receptor inhibition range in pre-procedure VerifyNow testing. Follow-up VerifyNow testing was performed in 32 patients (35.6%), which revealed that 33.3% of patients who had initially been within the target PRU range exhibited a "conversion" to a hyper-response to a daily 75mg clopidogrel dose (mean 15.2 PRU, median 8 PRU, range 1–59 PRU). We found no increased likelihood of P2Y12 receptor over-inhibition in patients on a selective serotonin reuptake inhibitor (18.8%), or P2Y12 receptor under-inhibition in patients on a proton pump inhibitor (9.1%). Conclusion: We found wide variability in patient response after 6–9 daily 75mg clopidogrel doses, with 20% of patients exhibiting P2Y12 receptor over-inhibition (PRU>60) and 16% of patients exhibiting P2Y12 receptor under-inhibition (PRU>240). Disclosures: J. Delgado Almandoz: 2; C; Covidien/ev3. Y. Kadkhodayan: None. J. Scholz: None. B. Crandall: 2; C; Covidien/ev3. J. Fease: None. R. Anderson: None. D. Tubman: 2; C; Covidien/ev3, MicroVention.